2017
DOI: 10.1016/j.chemgeo.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Trace element homogeneity from micron- to atomic scale: Implication for the suitability of the zircon GJ-1 as a trace element reference material

Abstract: Trace element homogeneity from micron-to atomic scale: Implication for the suitability of the zircon GJ-1 as a trace element reference material. Highlights The zircon reference material GJ-1 shows micron-to atomic scale chemical and structural homogeneity  GJ-1 can be used as a reference material for U-Th-Pb dating and Lu-Hf isotopic studies, but also for trace element analysis  GJ-1 combines structural and chemical homogeneity with chemical abundance and large sample size and volume  Atom probe tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 65 publications
1
16
0
1
Order By: Relevance
“…In spite of significant differences in trace element mass fractions, different SA01 zircon shards are characterised by consistent chondrite‐normalised REE patterns, namely depletion in LREE, enrichment in HREE, positive Ce anomaly and negligible Eu anomaly. Compared with the widely used zircon reference materials 91500 (Wiedenbeck et al ), Mud Tank (Woodhead and Hergt ), CZ‐3 (Pidgeon et al ), OG1 (Stern et al , Kemp et al ), Temora (Black et al ), Plešovice (Slama et al , Ver Hoeve et al ), GJ‐1 (Jackson et al , Piazolo et al ), GZ7/GZ8 (Nasdala et al ) and Qinghu (Li et al ), SA01 zircon is distinct with high Ti mass fractions and Th/U ratios (Figure f; Kirkland et al ). It is very common that zircons crystallised in alkaline magmas have high Ti mass fractions and high Th/U ratios (Fu et al , Peng et al , Zhu et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of significant differences in trace element mass fractions, different SA01 zircon shards are characterised by consistent chondrite‐normalised REE patterns, namely depletion in LREE, enrichment in HREE, positive Ce anomaly and negligible Eu anomaly. Compared with the widely used zircon reference materials 91500 (Wiedenbeck et al ), Mud Tank (Woodhead and Hergt ), CZ‐3 (Pidgeon et al ), OG1 (Stern et al , Kemp et al ), Temora (Black et al ), Plešovice (Slama et al , Ver Hoeve et al ), GJ‐1 (Jackson et al , Piazolo et al ), GZ7/GZ8 (Nasdala et al ) and Qinghu (Li et al ), SA01 zircon is distinct with high Ti mass fractions and Th/U ratios (Figure f; Kirkland et al ). It is very common that zircons crystallised in alkaline magmas have high Ti mass fractions and high Th/U ratios (Fu et al , Peng et al , Zhu et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Chondrite‐normalised REE patterns of intra‐grain analyses of three shards in (a–d) session 1 and (e) 2; (f) Th/U ratios versus Ti contents (μg g −1 ) of different zircon reference materials and SA01 zircon (data for zircon reference materials are from Li et al , Kirkland et al , Piazolo et al , Nasdala et al , and Ver Hoeve et al ; alkaline rocks data from Peng et al ). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…In particular, zircon and badelleyite reference materials have been used to confirm chemical quantification and to optimise acquisition conditions for these minerals [18,43 46]. Conversely, APM has been employed to test the nanoscale homogeneity of existing geostandards [47]. Others have also reported comparisons between APM chemical and isotopic compositions with those from standard materials or other well-characterised samples [26,28,32].…”
Section: Reference Materials and Standardisationmentioning
confidence: 99%
“…Recent work has shown that chemical values derived from APM of zircon, at length scales of the specimen needle and below, are precise and reasonably accurate, though minor artefacts may arise depending on the analysis conditions [44,46]. A current effort from eight APM laboratories around the world is investigating these effects systematically using a reference material used in zircon geochronology [47], which has been shown to be chemically homogeneous at the nanometer scale. In the future, such rigorous evaluation of the accuracy of APM data will be necessary for other minerals.…”
Section: Standardisation Of Analytical Procedures and Data Analysismentioning
confidence: 99%
“…APT couples chemical sensitivity and three-dimensional capabilities with a spatial resolution near the atomic scale to provide unique information about nanoscale structures. The technique has been demonstrated as a valuable tool to complement SIMS and allow for smallest-scale geochronology (e.g., [103]), to understand nanoscale diffusion within zircon [104,105], and for the examination of homogeneity within geochronological reference materials [106].…”
Section: Atom Probe Tomography (Apt)mentioning
confidence: 99%